Determining the relationship of financial leverage on return on equity in Malaysia : empirical evidence from Bursa Malaysia / Anas Abdul Imam Basirun - Abdul Imam Basirun, Anas (2019)
The purpose of this project paper is to determine the relationship between financial leverage and return on equity in Malaysia, with empirical result. This study selects 30 listed company in Bursa Malaysia randomly for the quarterly period 2014 - 2018. The method used in this project paper is unit root test and diagnostic check to get unbiased result. This study adopted both descriptive and descriptive analysis in describing the data set and in investigating the relationship between financial leverage and return on equity. Findings from the regression analysis reveal the insignificant relationship between financial leverage and return on equity in Malaysia. The regression result reveals that debt ratio has positive relationship on return on equity while debt equity ratio and interest coverage ratio reveal negative realtionship to return on equity.